Analysis of Physical and Mechanical Propoerties of Composite Board Made From Bamboo Fiber and Polyester Resin - Silviana Simbolon; Sulanjari Sulanjari; Ihat Solihat (Prodi Teknik Mesin, 2023)
The study was conducted to determine the characteristics of bamboo fiber reinforced composite materials. Composite samples were made with fiber composition in percent weight, namely 20%, 30%, 40% and as a matrix material using polyester resin. Then the bamboo fiber and matrix are mixed according to the composition and stirred manually until evenly distributed. Furthermore, the mixture of raw materials is poured into a mold and then left for 60 minutes, then the sample is released from the mold and cut into pieces according to the shape of the test specimen. The dried sample is tested which includes density test and compressive strength test. From the test results obtained that The mixing composition has a significant effect on the density and compressive strength of the composites. The density and compressive strength values in the composite with 20% bamboo fiber were 1.55 g/cm3 and 270 kgf/cm2 , while the sample with the composition of 30% bamboo fiber obtained density values of 1.48 g/cm3 and compressive strength of 274 kgf / cm2 . A sample with 40% bamboo fiber has density and compressive strength of 1.24 g/cm3 and 284 kgf/cm2 . The results of the sound absorbance test on bamboo fiber show that the percentage of sound absorption increases linearly as shown in the graph.